Comparison of peripheral endothelial dysfunction and intimal media thickness in patients with suspected coronary artery disease. Issue 4 (1st October 1998) - Enderle, M-D; Schroeder, S; Ossen, R; Meisner, C; Baumbach, A; Haering, H U; Karsch, K R; Pfohl, M
Abstract : Objective: Flow associated dilatation (FAD%) and intimal media thickness are established markers of early atherosclerosis. This study aimed to compare the ability of the non-invasive measurements FAD% and intimal media thickness to predict coronary artery disease. Methods: FAD% and intimal media thickness were determined using high resolution ultrasound in 122 patients with clinically suspected coronary artery disease before coronary angiography. Results are given as mean (SD). Results: Patients with coronary artery disease had reduced FAD% compared with those with angiographically normal coronary vessels (3.7 (4.1) v 7.0 (3.5)%, p < 0.001), whereas intimal media thickness tended to be increased in patients with coronary artery disease (0.58 (0.35) v 0.47 (0.11)mm, p = 0.054). There was a negative correlation between FAD% and intimal media thickness ( R = −0.317, p = 0.0004). Receiver operating characteristic analysis showed that FAD% ⩽ 4.5% predicted coronary artery disease with a sensitivity of 0.71 (95% confidence interval 0.61 to 0.80) and a specificity of 0.81 (0.58 to 0.95). In contrast, intimal media thickness showed a positive correlation with the extent of coronary artery disease (number of vessels with a lesion ⩾ 50%) ( R = 0.324, p = 0.0003), without a clear cut off point. Conclusions: In patients with clinically suspected coronary artery disease, FAD% discriminates between the presence or absence of coronary artery disease, whereas intimal media thickness is associated more with the extent of coronary artery disease.